Characteristics of Wave Reflection for Vertical and Slit Caissons with Porous Structures - Tae-Hwa Jung; Sung-Jae Lee; Yong-Sik Cho (Journal of Applied Mathematics)
Offshore structures are occasionally located at a relatively deep water region, the outside of breakwater. In this case, these structures may be damaged by the supposition of incident and reflected waves from a vertical breakwater. To prevent the damage, the reflected waves are controlled by installing porous structures at the face of the vertical breakwater. In this study, numerical experiments are carried out to identify the characteristics of wave reflection from the porous structures installing in front of a vertical or slit caisson.